The effect of silicone on some properties of flakeboard - Jusoh, Ismail B.; Nzokou, P.; Kamdem, P. (SpringerLink, 2005)
Waxes are used as water repellent in wood composites, and there are only limited alternative waterrepellent systems for wood composites. The aim of this study was to investigate the effectiveness of a silicone compound as a water repellent for flakeboard and to compare the properties of boards made with silicone treated flakes to those made with commercial wax treated flakes. Three levels of silicone and wax application rates were used (0.25, 0.5, and I %). The hydrophobic nature of silicone-treated flakes was evaluated by measuring the contact angle and the rate of water absorption (W A) on the surface of the wood flake. The internal bonding strength (IB), the modulus of elasticity (MOE) and modulus of rupture (MOR) in bending regime, the W A, and the thickness swelling at edges of boards were evaluated. Results obtained showed that IB, MOE and MOR decreased as the concentration of silicone on the flakes increased from 0.25% to 1%. The IB, MOE and MOR of panels made with 0.25% siliconetreated flakes were comparable to boards made with 1% wax-treated flakes. Thickness swell at edges and WA were significantly reduced as the amount of silicone increased. No significant difference was found for the thickness swelling at edges and the W A between panels made with I % silicone-treated flakes and 1% waxtreated flakes. The silicone treated flakes had high water repellency.